2021
DOI: 10.1021/acs.jmedchem.0c01656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition and Imaging of Human Telomeric G-Quadruplex DNA in Live Cells: A Systematic Advancement of Thiazole Orange Scaffold To Enhance Binding Specificity and Inhibition of Gene Expression

Abstract: A series of fluorescent ligands, which were systematically constructed from thiazole orange scaffold, was investigated for their interactions with G-quadruplex structures and antitumor activity. Among the ligands, compound 3 was identified to exhibit excellent specificity toward telomere G4-DNA over other nucleic acids. The affinity of 3-Htg24 was almost 5 times higher than that of double-stranded DNA and promoter G4-DNA. Interaction studies showed that 3 may bind to both G-tetrad and the lateral loop near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 52 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…We found that, apart from adopting a planar core molecular fragment to construct G4-ligands, the overall molecular size, 116 symmetry, 117,118 flexibility, 83 and the character of terminal groups 119–122 may affect the in vitro selectivity of the ligand toward G4-structures against RNA, single- and double-stranded DNA. Our study suggests that some small-sized molecular scaffolds including benzothiazole-benzofuroquinolinium, 123,124 benzothiazole-indolium, 125 1-methylquinolinium, 126 thiazole orange 81,84,127 and benzo[ e ]indole 128 are good molecular fragments for the design of fluorescent G4-ligands to achieve high discrimination ability, sensitivity and quantum yield targeting certain types of G4s for in vitro sensing and live cell imaging. In the design of G4-ligands, the molecular symmetry of G4-ligands has been rarely discussed in the literature.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 89%
“…We found that, apart from adopting a planar core molecular fragment to construct G4-ligands, the overall molecular size, 116 symmetry, 117,118 flexibility, 83 and the character of terminal groups 119–122 may affect the in vitro selectivity of the ligand toward G4-structures against RNA, single- and double-stranded DNA. Our study suggests that some small-sized molecular scaffolds including benzothiazole-benzofuroquinolinium, 123,124 benzothiazole-indolium, 125 1-methylquinolinium, 126 thiazole orange 81,84,127 and benzo[ e ]indole 128 are good molecular fragments for the design of fluorescent G4-ligands to achieve high discrimination ability, sensitivity and quantum yield targeting certain types of G4s for in vitro sensing and live cell imaging. In the design of G4-ligands, the molecular symmetry of G4-ligands has been rarely discussed in the literature.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 89%
“…Over the past decades, intense research has focused on developing small-molecule fluorescent probes for monitoring G4s in cells, offering means to the relevant investigations of G4 structures and function in cellular studies. Although some G4-binding dyes have been developed, there are still limitations, such as the inability to visualize nuclear RNA G4s and relatively low signal-to-noise ratios. In this regard, a commercial benzothiazole dye thioflavin T (ThT) exhibits high selectivity and binding affinity toward G4 structures and directly visualizes the RNA G4s in cell nuclei. , By modulating the structure of molecules, an increasing number of ThT analogues have been engineered, which are applied in the real-time imaging of DNA G4 and viral RNA G4.…”
Section: Introductionmentioning
confidence: 99%
“…GQ-forming sequences have been found in the genomes of many organisms, ranging from viruses [23][24][25][26][27] to bacteria [28][29][30][31] and malaria [32][33][34]. GQs have been visualized in fixed [35][36][37][38] and in live cells [39][40][41][42], where their existence may be more than transient, with several roles in gene function [3,4,12]; for example, GQ folding is associated with sites of active transcription and precedes transcription itself [13,22].…”
Section: Introductionmentioning
confidence: 99%